The Potential Usage of Bitumen Cold Mix and Tire Chips as Stabilization Material on Clay Soil Strength Characteristics - Mulyanda, Dhevi (Universitas Negeri Padang, 2023)
Clay is a soil with fine particle size less than 0.002 mm, low permeability, cohession, high swelling, and slow consolidation process. Due to that problem it needs some improvement to stabilize the condition of soil before the process of construction conducted. The purpose of this study is to determine the effect of adding shredded tire and cold mix bitumen as the value of shear strength changing are cohession, friction angle, and shear strength with triaxial unconsolidated undrained test. To see the effect of those mixture, this study uses 48 soil samples with 4 variation of shredded tired (0%, 1%, 1,5%, and 2%) and 4 variation of cold mix bitumen (0%, 1%, 2%, dan 3%). The result of this study showed that the adding of shredded tired and cold mix bitumen in soil compositition can increase parameters of soil. The optimum cohession is on variation 1% SB+2% B (T99B2SB1) with the value 0.61 kg/cm2. Meanwhile the optimum value of friction angle is on variation 1.5% SB+ 1% B (T98.5B1SB1.5) with the value 7.43o. The shear strength as the sum of cohession and friction angle tends to increase with the optimum value about 0.995 kg/cm2 in variation 2% bitumen and 1% shredded tire (T99B1SB1). From the study, the adding of shredded tired and cold mix bitumen improve the shear strength. The optimum value of shear strength is on variation 2% B+1% SB (T99B1SB1) with the value 0.995 kg/cm2. This study shows that stabilization material used in this research can be an alternative material for soil stabilization.